ANALISIS YURIDIS TERHADAP TINDAK PIDANA PORNOGRAFI MELALUI MEDIA ELEKTRONIK BERDASARKAN KETENTUAN HUKUM POSITIF - Pamungkas, Satria Jati; Riyanto, Agus (SCIENTIA JOURNAL, 2019)
This research tries to describe how prevention of cyber pornograph and online prostitution using social media facilities in Criminal Law in Indonesia and how law enforcement is done by City Police Departement of Riau Kepulauan about criminal cyber pornograph and online prostitution using social media. The type of research on this thesis is empirical juridical research that is the way or procedure used to solve the research problem by researching the secondary data first to then examine the primary data in the field. The author performs the necessary data collection techniques through Library Research and Field Research. Data analysis method used is descriptive analysis. Cyber pornograph and online prostitution using social media in the Criminal Law in Batam still lacks in relation to its Section formula. Law enforcement conducted by City Police Departement of Riau Kepulauanon the cyber pornograph and online prostitution using social media has not been effective resulting in many similar crimes still encountered.